Preparation of Non-Covalent BPTCD/g-C3N4 Heterojunction Photocatalysts and Photodegradation of Organic Dyes Under Solar Irradiation - Xing Wei; Gaopeng Jia; Ru Chen; Yalong Zhang (Nanomaterials, 2025)
In this study, the BPTCD/g-C3N4 heterojunction photocatalyst was successfully prepared by the hydrothermal method. BPTCD (3,3′,4,4′-benzophenone tetracarboxylic dianhydride) is immobilised on the surface of g-C3N4 by non-covalent π-π stacking. The BPTCD/g-C3N4 heterojunction photocatalyst is an all-organic photocatalyst with significantly improved photocatalytic performance compared with g-C3N4. BPTCD/g-C3N4-60% was able to effectively degrade MO solution (10 mg/L) to 99.9% and 82.8% in 60 min under full spectrum and visible light. The TOC measurement results indicate that MO can ultimately be decomposed into H2O and CO2 through photocatalytic action. The photodegradation of methyl orange by BPTCD/g-C3N4 composite materials under sunlight is mainly attributed to the successful construction of the heterojunction structure and its excellent π-π stacking effect. Superoxide radicals (•O2−) were found to be the main active species, while •OH and h+ played a secondary role. The synthesised BPTCD/g-C3N4 also showed excellent stability in the activity of photodegradation of MO in wastewater, with the performance remaining above 90% after three cycles. The mechanism of the photocatalytic removal of MO dyes was also investigated by the trap agent experiments. Additionally, BPTCD/g-C3N4-60% demonstrated exceptional photodegradation performance in the degradation of methylene blue (MB). BPTCD/g-C3N4 heterojunctions have great potential to degrade organic pollutants in wastewater under solar irradiation conditions.